2016
DOI: 10.1061/(asce)be.1943-5592.0000775
|View full text |Cite
|
Sign up to set email alerts
|

Bridge Decks with Precast UHPC Waffle Panels: A Field Evaluation and Design Optimization

Abstract: The first full-depth precast ultrahigh-performance concrete (UHPC) waffle panels have been designed and implemented in a bridge replacement project to use accelerated bridge construction and increase bridge deck longevity. This paper first evaluates the structural performance of this bridge using a combination of field liveload testing and analytical modeling. The collected data for vertical deflections and strains at discrete critical locations on the bridge deck, subjected to static and dynamic truck loads, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…In recent years, various constructions have been realized with UHPFRC in structural and civil engineering (e.g., references 59–62). Nevertheless, the higher binder content of these concretes results in higher energy consumption and CO 2 emissions.…”
Section: High Performance Materialsmentioning
confidence: 99%
“…In recent years, various constructions have been realized with UHPFRC in structural and civil engineering (e.g., references 59–62). Nevertheless, the higher binder content of these concretes results in higher energy consumption and CO 2 emissions.…”
Section: High Performance Materialsmentioning
confidence: 99%
“…Recently, many bridges were constructed using closure joints made of straight reinforcing bars with UHPC (Honarvar et al, 2016;Rallabhandhi, 2016;Semendary et al, 2017). UHPC is a cementitious composite material with very high compressive strength, high tensile strength, and excellent durability properties.…”
Section: Closure Joint Typesmentioning
confidence: 99%
“…So far, there have been a number of experimental and analytical studies in this field [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], with an increasing applications of UHPC waffle deck for new constructions and the replacement of concrete deck in the existing bridges. The field evaluation of the first bridge, using prefabricated UHPC waffle deck, was conducted by Honarvar et al [ 21 ], and the design optimization was suggested. Up to now, the longitudinal flexure [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 20 ], shear [ 19 ], fatigue behavior [ 10 ], and connector of steel-UHPC waffle bridge deck [ 11 ] have already been reported, but it is rare to see a study on the transverse flexural behavior.…”
Section: Introductionmentioning
confidence: 99%